OPTIMIZATION OF STEEL PROFILE DIMENSIONS AND BOLT CONNECTIONS IN INTAKE STRUCTURES FOR ENHANCED STRUCTURAL INTEGRITY - Costa, Anthony; Adhitya, Bimo Brata; Sadila, Yunira; Rosidawani, Rosidawani (Asosiasi Peneliti Sriwijaya, 2024)
Intake structures are facilities for clean water supply situated along riverbanks. These structures are reinforced concrete with pile foundations, and the intake structure comprises a profiled steel frame serving as the upper column-beam framework. The implementation of steel structures demands a high level of precision, particularly in designing connections between sectional steel beams and columns. This study, therefore, aims to determine the optimal dimensions for steel profiles by referring to the design of bolt connections as specified in SNI 1729-2020, particularly for steel beam columns subjected to pump loads and load combinations. The analysis concludes that all three material types meet the safety criteria, with a structural ratio value of ≤ 1 and structural deflection within the allowable limits. Additionally, after assessing the steel column and beam sections' capacity to bear pump loads, it was determined that the optimal bolt connection involved 8 bolts of 24 mm diameter. The ideal supplementary steel plate connection required a plate thickness of 13 mm.